Relationship between pain, function and radiological findings in osteoarthritis of the knee - Saiful Arif, M.; Sultan, Mohammad Imtiaz; Dey, Protyay; Deb, Aparna; Islam, Mohammed Taherul; Majumder, Suvash; Tasnim, Sanjida; Dee, Deepannita (International Journal of Research in Medical Sciences, 2026)
Background: Osteoarthritis (OA) is the most common degenerative joint disorder and a major public health problem throughout the world. Knees are the most commonly affected joints. There is ongoing debate on whether an association exists between radiographic and clinical features of OA. Purpose of this study was found out the relationship between pain, function and radiographic findings in OA. Methods: At first subjects who attend OPD and IPD of CMCH with knee pain and fulfill ACR 1991 OA classification criteria, and also fulfilling preset inclusion and exclusion criteria, was interviewed and send to department of radiology to have three views of radiograph of index knee that is skyline, Rosenberg and lateral and to measure radiologic parameters across all three compartments of knee joint along with alignment. Results: In this study, out of 96 patients, mean±SD age of the patients was 59.59375±8 years, 55.2% was female and 47.1% had primary level of education, mostly female, urban, and over 50 years. All met ACR criteria with predominant right knee involvement and a mean disease duration of 6.2 years. Radiographic changes were common across compartments, mainly Kellgren-Lawrence (K-L) grades II-III. WOMAC pain, stiffness, and disability correlated significantly with disease severity, duration, age, and gender. Conclusions: Radiographic findings were associated with pain in activity and functional status based on physical performance. Disability scores were associated with pain and stiffness. WOMAC index was statistically significant between KL grading. Varus angle and male gender were for risk of having predominantly OA.